Consumers’ preferences for perceptual and sensory attributes of chicken meat in Malaysia - Imran, Siti Nasihah (2015)
Meat plays an important role in a balanced diet as a source of protein intake. Since the demand for chicken meat is high among consumers, many producers try to meet this demand by producing a fast-growing chicken by increasing the efficiency of their production through enhancing genetics, management, housing environment, nutrition,and animal health. The increasing consumer awareness of health issues has caused them to be very sensitive on food consumption. Meat consumption patterns have a significant effect on the changes in consumer demand for meat. The increasing rate of female labour force participation, improved per capita income, rising rate of urbanization, as well as lifestyle changes resulting in urbanization are predicted to further increase the demand for quality meat in the country. For most consumers,sensory characteristics like appearance, texture, odour, and flavour are the initial preference criteria when purchasing chicken meat. Now, consumers have greater choices for different types of chicken meat in the market. Consumers’ preference depends to the best quality of chicken meat based on sensory characteristics. Thus, the objective of this study was to determine consumers’ preference towards different types of chicken meat based on sensory characteristics. Sensory evaluation was used to analyse the haracteristics among four different types of chicken meat namely commercial broiler chicken, commercial village chicken [intensive], village chicken [semi-intensive], and herbal organic chicken. Face-to-face interviews were carried out at the Central Location Place with 569 consumer panels. Stratified sampling method was used to select the targeted respondents. Consumers’ acceptance and preference on chicken meat were based on a 9-point hedonic scale ranging from 1 (dislike extremely) to 9 (like extremely), while consumers’ perception on chicken meat was based on a 5-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree). Data was analysed using descriptive analysis, analysis of variance (one-way ANOVA), chi-square analysis, mean ranking analysis, factor analysis, and logistic regression. Based on the results of descriptive analysis, majority of the respondents were female,married, age between 18 years old to 30 years old. Most of the respondents were Malay, Muslim, and originated from the Central Zone area. Most of them have less than six numbers of household, were degree holders, had working experience in the private sector, and earned monthly income between RM1,001 to RM3,000. In general,consumers consumed chicken at least two to three times per week and the most preferred chicken meat was commercial broiler chicken. The findings based on the analysis of variance (one-way ANOVA) indicated that most of the consumers preferred moderately light colour herbal organic chicken, and slightly weak chicken aroma of herbal organic chicken. However, for texture and flavour characteristics such as tenderness, juiciness, springiness, fibrousness, and sweetness;consumers preferred village chicken (semi-intensive). Consumers also preferred slightly tender, slightly juicy, moderately springy, slightly not fibrous, and slightly strong sweetness of village chicken (semi-intensive). Unfortunately, consumers showed the least preference on the characteristics of commercial broiler chicken meat. The results from chi-square analysis indicated gender and income as significant to consumers’ preferences based on sensory characteristics when deciding on buying chicken meat. It was revealed that demographic variables such as region, age, race, religion, marital status, education level, occupation, and number of household were not significant. Based on mean ranking analysis, most of the consumers preferred chicken with less fat and liked tender chicken meat because it was delicious. The consumers also believed that chicken feed influenced taste and odour of chicken meat. Nevertheless, consumers claimed that they dislike chicken meat with thicker skin. Meanwhile, the results of factor analysis revealed that nine factors such as colour, size, springiness, chicken aroma, fatty/oily taste, sweetness, visibility of fat, tenderness, and fibrous influenced consumers’ perception towards chicken meat quality based on sensory characteristics. Finally, the findings of logistic regression proved that gender, income, colour,springiness, sweetness, visibility of fat, and tenderness represented the most important factors influencing consumers’ preference towards chicken meat quality when deciding to purchase. Nevertheless, variables of age, education level, occupation, size, chicken aroma, fatty/oily taste, and fibrous were not significant in the model. As a conclusion, the results obtained from the analyses have provided evidence that different types of chicken meat showed different sensory characteristics. Consumers preferred the sensory attributes of village chicken [semi-intensive] compared to commercial broiler chicken. Different socio-demographic profiles of consumers also influenced the buying decision of chicken meat. Gender and income are found to be significant on buying decision. Tenderness attribute is the major attribute that influenced consumers’ preference towards chicken meat quality. This study provides a valuable guidance to producers, industry players, marketers, and policy makers to fully understand consumers’ preferences by providing the intrinsic quality cues of the chicken meat especially on sensory characteristics.